-5 is the answer -20a divided by 4a is -5. If we times 4a by a positive number, we would get a positive number, so we have to times it by a negative number. The number can't have an a at the end as this would mean when we times it by 4a we would end up with a2 -5 x 4 = -20 then we add on the a = -20a
a = -2-4a/3-2 = 8-4a = 8(3-2) times both sides by (3-2)-4a = 24-16-4a = 8-a = 2 divide both sides by 4a = -2 times both sides by -1
Add them together: 3a+4a-a = 6a
You have to multiply base x height - in this case, you obtain (4a)(2a+b). This can't be simplified; you can leave it as it is (factored), or multiply it out to obtain 8a2 + 4ab.
It is an expression of two terms as: 4a+12
When you multiply 2a by 2a, you are essentially multiplying 2 by 2 and a by a separately. This results in 4a^2, where the coefficient 4 is the product of 2 and 2, and a^2 represents a multiplied by a. Therefore, the final answer is 4a^2.
4a x 3
x2=(4a)(a) x=√4a2 x=2a The geometric mean of a and 4a is 2a
4a*2c=8ac
American Association of Advertising Agencies: 4A's
4a x 4b = 16ab Variables can be multiplied just like numbers.
Factor them. 2 x 2 x a = 4a 2 x 5 x a x a = 10a2 Select the common factors. 2 x a = 2a, the GCF.
4a
30
10
Factor them. 2 x 2 x a = 4a 2 x 5 x a x a = 10a2 Combine the factors, eliminating duplicates. 2 x 2 x 5 x a x a = 20a2, the LCM
The general equation of a parabola is y = ax2 + bx + c.The vertex of a parabola is (-b/2a, c - b2/4a). In our case the vertex is (2, -4). So we have,-b/2a = 2, so that b = -4a, andc - b2/4a = -4 (substitute -4a for b)c - (-4a)2/4a = -4c = 16a2/4a = -4 (simplify)c - 4a = -4 (solve for c)c = 4a - 4By substituting -4a for b, and 4a - 4 for c, the equation becomes,y = ax2 + bx + cy = ax2 + (-4a)x + 4a - 4Since it is given that when x = -3, y = -3, we substitute them into the new equation and solve it for a. So we have,y = ax2 + (-4a)x + 4a - 4-3 = a(-3)2 + (-4a)(-3) + 4a - 4-3 = 9a + 12a + 4a - 4 (add 4 to both side, and add alike terms on the right-hand side)1 = 25a (divide by 25 to both sides)1/25 = a (this is the required answer)If you want to find the equation of the parabola, just substitute 1/25 for a, such as:y = ax2 + (-4a)x + 4a - 4y = (1/25)x2 + [-4(1/25)]x + 4(1/25) - 4y = (1/25)x2 -4/25x + 4/25 - 4y = (1/25)x2 -4/25x + 96/25